Pengaruh Partisipasi Anggaran Terhadap KinerjaManajerial Dengan Motivasi Dan BudayaOrganisasi Sebagai Variabel Moderasi(Studi Kasus pada Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta) - Yulianingsih, Yatik, Dr. Fatchan Achyani, SE, M.Si (2017)
The purpose of this study was to determine the effect of budget participation on managerial performance with motivation and organizational culture as a moderating variable. This research was conducted at BBKPM Surarakarta. The samples in this study using saturated sampling method. The data in this research is obtained by distributing questionnaires to the respondents. Samples in this study as many as 45 managers. The data analysis was using multiple linear regressions analysis. The results showed that the budget does not effect the participation of managerial performance, the interaction between budgetary participation and motivation no effect on managerial performance, and the interaction between budgetary participation and influence organizational culture on managerial performance.